DNA methylation regulates CHRNA7 transcription and can be modulated by valproate. (21st June 2019) - Dyrvig, Mads; Mikkelsen, Jens D.; Lichota, Jacek
Highlights: The α7 nicotine receptor is considered a promising drug target for treatment of cognitive dysfunction in schizophrenia. Promoter regions of NACHR7 gene have been identified and checked for DNA methylation. In vitro model cell lines exhibit different patterns of NACHR7 DNA methylation. Treatment with nicotine and valproate changes DNA methylation and influences NACHR7 gene transcription. Genotypic variations influence methylation levels of the CHRNA7 promoter. Abstract: The CHRNA7 gene encoding the α7 nicotinic acetylcholine receptor (nAChR) has repeatedly been linked with schizophrenia and the P50 sensory gating deficit. The α7 nAChR is considered a promising drug target for treatment of cognitive dysfunction in schizophrenia and improves memory and executive functions in patients and healthy individuals. However, clinical trials with pro-cognitive drugs are challenged by large inter-individual response variations and these have been linked to genotypic variations reducing CHRNA7 expression and α7 nAChR function. Genetic variants as well as environmental conditions may cause epigenetic dysregulation and it has previously been found that DNA methylation of a region surrounding the transcription start site of CHRNA7 is important for tissue specific regulation and gene silencing. In the present study we identify two additional regions involved in epigenetic regulation of the CHRNA7 promoter. In human temporal cortex we find large variations in expression of CHRNA7 and establish evidence for a significant correlation with DNA methylation levels of one region. We then establish evidence that genotypic variations can influence methylation levels of the CHRNA7 promoter. Epigenetic dysregulation can be reversed by pharmacological intervention and in HeLa cells. Valproate, a commonly used mood stabiliser, caused demethylation and increased CHRNA7 expression in HeLA cells. Similar demethylation effect and increased CHRNA7 expression was obtained in SH-SY5Y cells stimulated concomitantly with valproate and nicotine. In summary, both genetic and epigenetic information could be useful to predict treatment outcomes in patients and epigenetic modulation may serve as a mechanism for potentiating the effects of α7 nAChR agonists.